Isolation of NDM-1-producing multidrug-resistant Pseudomonas putida from a paediatric case of acute gastroenteritis, India. (May 2015) - Bhattacharya, D.; Dey, S.; Kadam, S.; Kalal, S.; Jali, S.; Koley, H.; Sinha, R.; Nag, D.; Kholkute, S.D.; Roy, S.
Abstract: Pseudomonas putida is an uncommon opportunistic pathogen, usually susceptible to antimicrobial agents. Data concerning resistance to antimicrobial agents in clinical P. putida isolates are limited. To the best of our knowledge we report for the first time the isolation of NDM-1 -producing multidrug-resistant P. putida from a case of acute gastroenteritis. The isolate showed resistance to a wide range of antimicrobials, including fluoroquinolones, third-generation cephalosporins and carbapenems. The isolate also exhibited multiple mutations in the quinolone resistance determining region and showed the presence of qepA, bla TEM, bla OXA1 and bla OXA7 genes. The present study highlights the importance of looking for the relatively rare aetiological agents in clinical samples that do not yield common pathogens.